The Luck Uglies - Durham, Paul (Paul Joseph), 1972-; d (New York : Harper, 2014)
Eleven-year-old Rye O'Chanter and her two friends delve into the secret lore of their village when mysterious creatures of legend reappear on the night of the Black Moon.
School Library Journal, March 2014
Kirkus Starred, February 2014
5.5
3-6
OBOB 2018-2019
Keywords: Adventure and adventurers -- Fiction; Fantasy; Monsters -- Fiction; Secret societies -- Fiction; Adventure fiction; Fantasy fiction; Adventure fiction; Fantasy fiction